A comparative study on women’s right to terminate pregnancy in Egypt and Vietnam - Lâm, Tố Trang (Edelweiss Applied Science and Technology, 2025)
Pregnancy and childbirth are among the sacred responsibilities that nature has bestowed upon women. However, for one or more reasons, sometimes women have to terminate their pregnancies. The right to terminate their pregnancies, or the right to abortion, is always an issue with many different views around the world. Before discussing the views on supporting or not supporting women’s right to terminate their pregnancies, the article presents the definition and classification of termination of pregnancy and, at the same time, introduces the methods of termination of pregnancy currently applied in the world. Although, medically, termination of pregnancy can be performed under certain conditions without endangering the life of the pregnant women, for religious reasons, termination of pregnancy is sometimes not recognized in some countries. Based on the international legal documents related to the right to terminate pregnancies that member states of these documents have ratified, the article analyzes the current legal regulations on the right to abortion in Egypt and Vietnam. Therefore, some recommendations are proposed in the legal system of Egypt and Vietnam in order to ensure women’s right to abortion in these countries.